2006
DOI: 10.1532/ijh97.05105
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Neutropenia in Patients Treated with Rituximab for Non-Hodgkin's Lymphoma

Abstract: Late-onset grade 4 neutropenia occurred in 3 (5.6%) of 54 non-Hodgkin's lymphoma patients treated with rituximab between September 2001 and March 2004. Neutropenia appeared 5 to 25 weeks after administration of cytotoxic agents in combination with rituximab and recurred 4 and 17 weeks after the first onset in 2 patients. Five episodes occurred in a total of 332 cycles of rituximab therapy. Bone marrow findings at the time of late-onset neutropenia showed neutrophil maturation arrest with or without reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…In further support of this notion, Voog et al [14] identified eight patients with LON and detected antineutrophil antibodies in two of these patients. However, the absence of anti-neutrophil antibodies in other studies [8,10,11,21,22] suggests that additional factors are also involved in LON.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In further support of this notion, Voog et al [14] identified eight patients with LON and detected antineutrophil antibodies in two of these patients. However, the absence of anti-neutrophil antibodies in other studies [8,10,11,21,22] suggests that additional factors are also involved in LON.…”
Section: Discussionmentioning
confidence: 86%
“…The erythropoiesis is left-shifted and shows megaloblastoid features. There is impaired maturation in the granulocytopoeisis with abundant promyelocytes (arrows), although some rods and mature neutrophils are seen duration from 1 week to 1 month in the literature [7][8][9][10][11][12][13][14]. This is much higher than post-marketing reporting rates of LON 0.02% [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One theory is that neutropenia arises from impaired myelopoiesis due to altered growth factors and/or competition between cell lineages in the marrow niche during homeostatic restoration of B cells (Dunleavy et al 2005;Terrier et al 2007). Alternatively, Fas-mediated apoptosis of neutrophils by increased Fas associated with expansion of reactive granular T lymphocytes has been demonstrated by one group (Stamatopoulos et al 2008) but has not been confirmed by other investigators (Fukuno et al 2006;Terrier et al 2007;Tesfa et al 2008).…”
Section: Rituximabmentioning
confidence: 92%
“…One mysterious toxicity of RTX is late-onset neutropenia (LON). LON, defined as an absolute neutrophil count (ANC) <1.5 × 10 9 /L occurring greater than 4 weeks after the last dose of RTX without another identifiable cause, has been reported after administration for hematologic malignancies [9][10][11] and recently in case series when given for rheumatologic disorders [12][13][14][15][16]. Patients usually present without symptoms and recover spontaneously, although patients may initially present with infections [17] of varying ranges of severity.…”
Section: Introductionmentioning
confidence: 99%